"Und weil der Mensch ein Mensch ist ...": interkulturelle Ethik, religiöse Identität und Konflikt - Schäfer, Heinrich Wilhelm (Sicherheit und Frieden, 2004)
Many contemporary conflicts are characterized by strong religious and cultural factors. This is where ethical prin ciples like the discursive »moral principle« of Karl - Otto Apel enter in difficulties. Intercultural ethics has to deal with the sin etwork of cultural and religious convictions of the actors implied in conflicts. The present article shows a method of how IIPEo link to such a network of a fundamentalist movement and to introduce slight but effective changes. But the concentrati on on thick cultural convictions - as communitarianists do - does not mean to leave basic humanitarian principles aside. The reflection on the preconditions of liberal ethical principles in bodily human life allows for an interculturally valid refe rence to a principle of universal humanity.